An upgraded storage site model of the Shenhua CCS demonstration project. (November 2018) - Diao, Yujie; Zhu, Guowei; Li, Xufeng; Bai, Bing; Wang, Yongsheng; Zhang, Bing; Long, Hui
Abstract: As the only project for CO2 storage in deep saline aquifers in China, the Shenhua CCS demonstration project is of great importance in the geological storage of CO2 in continental sedimentary strata. Despite achieving the designed injection goal of 302, 000 tons, the demonstration project currently does not have a widely accepted storage site geological model because of the large overall thickness of the injection layers, low porosity and permeability, and high heterogeneity. Based on geological study of the storage site system, combined with vertical seismic profiling (VSP) seismic monitoring data, we used the well log-constrained seismic inversion method to predict the lithology, porosity and permeability of the storage site. We constructed a new 5 km × 5 km × 1200 m site geological model centered on the injection well. Our new geological modeling method and the related reservoir parameters are innovative compared with previous studies and enhance geological understanding of the site, providing a reference for CO2 migration reservoir simulation and deep geophysical monitoring in the future stages of the project.